2021
DOI: 10.3367/ufne.2021.01.038918
|View full text |Cite
|
Sign up to set email alerts
|

Applied superconductivity: frustrations and hopes

Abstract: The alternation of bright triumphs generating far-reaching expectations and subsequent deep disappointments is a characteristic feature of the development of applied super-conductivity, associated with creating superconducting windings and winding wires. This, unfortunately, testifies to the inadequacy of scientific and technical foundations formed on the basis of several speculative hypotheses and a useful, but not quite accurate, model of the critical state. The protracted romantic period of evolution has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…One other problem is delay fault testing, where [9] proposes a DFT technique to reduce the number of logic gates used as test points in order to reduce the overhead area and the number of additional inputs. One of the DFT methods is the structured method, the scan-based method is the structured method, where this method is an alternative to the ad-hoc method which has weaknesses along with the size and complexity of the growing digital system [10]. The test method for the ISCAS'89 S1423 circuit in this study was carried out using a structured method because the circuit has a large number of flip flops [11], the test of this circuit is carried out in several stages, first the circuit will be downloaded in verilog form, the second is modifying the circuit in tetramax design vision so that it can be read properly, thirdly modifying the circuit by adding a scan-chain, after that the circuit is ready to be tested using a scan-based design method, which is full-scan and partial-scan.…”
Section: Methodsmentioning
confidence: 99%
“…One other problem is delay fault testing, where [9] proposes a DFT technique to reduce the number of logic gates used as test points in order to reduce the overhead area and the number of additional inputs. One of the DFT methods is the structured method, the scan-based method is the structured method, where this method is an alternative to the ad-hoc method which has weaknesses along with the size and complexity of the growing digital system [10]. The test method for the ISCAS'89 S1423 circuit in this study was carried out using a structured method because the circuit has a large number of flip flops [11], the test of this circuit is carried out in several stages, first the circuit will be downloaded in verilog form, the second is modifying the circuit in tetramax design vision so that it can be read properly, thirdly modifying the circuit by adding a scan-chain, after that the circuit is ready to be tested using a scan-based design method, which is full-scan and partial-scan.…”
Section: Methodsmentioning
confidence: 99%
“…Superconductivity (SC) is the property of some materials to possess strictly zero electrical resistance at temperatures below a certain critical temperature TC. More than 100 years of research on this phenomenon have not yet fully revealed the engineering and technical potential of the applications of superconductivity [1,2]; and the microscopic mechanisms of superconductivity are still being discussed. Despite the enormous effect that can be expected from the use of superconductors in various fields of engineering and technology, the scope of their actual practical application is still limited due to high costs for cooling significantly below the critical temperature, as well as due to technical difficulties and high cost of manufacturing multilayer materials of multicomponent composition.…”
Section: Introductionmentioning
confidence: 99%